Analisis Pendapatan Usahatani Sawi Hijau (Brassica Juncea L.) di Subak Bengkel Kecamatan Kediri Kabupaten Tabanan - Ni Putu Lisa Novia Cahyani; Nyoman Yudiarini; I Made Tamba (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Green mustard (Brassica juncea L.) is a prominent horticultural commodity in Subak Bengkel, Kediri District, Tabanan Regency, however, most farmers have not structured their farming costs and income records. This study aims to analyze the production costs, income, and feasibility of green mustard farming in this purposively selected location, known as a vegetable production center. The research employed a census method (saturated sampling) involving 105 respondent farmers, with data analyzed using cost, revenue, and income analysis, as well as feasibility tests using the Revenue Cost Ratio (R/C Ratio) and Benefit Cost Ratio (B/C Ratio). The results showed that with an average land area of 29 are, the average total production cost per planting season was IDR 4,786,905, while the average revenue reached IDR 20,453,225, resulting in a net income of IDR 15,666,320. Based on the feasibility analysis, it is concluded that green mustard farming in Subak Bengkel is highly feasible and profitable, with an R/C Ratio of 4.27 and a B/C Ratio of 3.27, indicating that every IDR 1.00 of expenditure generates a revenue of IDR 4.27 and a net profit of IDR 3.27.